Pengaruh Budaya Organisasi, Komitmen Organisasi, Kompensasi dan Etos Kerja terhadap Kinerja Karyawan - Shafikha Septiandri; Karel Tjahjadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Achieving business goals has challenges and gaps that need to be addressed effectively. The business should have a plan to address these issues, including work arrangements. Based on the results of discussions with the management of PT RH. X, employee productivity scores decreased from 2017 to 2020. The purpose of this study was to empirically examine the influence of organizational culture, organizational commitment, compensation, and morale on employee performance. The object used is the company PT. X used a sample of 71 manufacturing workers who were employed using a purposive sampling technique. The Likert scale was used in the questionnaire given to each respondent. In this study, multiple linear regression was used as a data analysis method. Surveys show that organizational culture, organizational commitment, compensation and work ethic have a positive impact on employee performance.